156 THE EXPRESSION AND ROLE OF ANO9 IN HUMAN ESOPHAGEAL SQUAMOUS CELL CARCINOMA. (17th September 2021) - Inoue, Hiroyuki; Shiozaki, Atsushi; Fujiwara, Hitoshi; Konishi, Hirotaka; Katsurahara, Keita; Kudou, Michihiro; Shimizu, Hiroki; Arita, Tomohiro; Kosuga, Toshiyuki; Morimura, Ryo; Kuriu, Yoshiaki; Ikoma, Hisashi; et al.
Abstract: : The anoctamin (ANO) family consists of transmembrane proteins in 10 isoforms, and ANOs are broadly expressed in epithelial and non-epithelial tissues. Few studies have reported the function and activation mechanism of ANO9 in esophageal squamous cell carcinoma (ESCC), and the clinical significance of its expression remains unclear. The aims of the present study were to investigate the role of ANO9 in the regulation of tumor progression and its clinicopathological significance in ESCC. Methods: In human ESCC cell lines KYSE150 and KYSE790, knockdown experiments were performed using ANO9 siRNA, and the effects on cell proliferation, cell cycle, apoptosis, invasion and migration were analyzed. The gene expression profiles of cells were examined using a microarray analysis. Immunohistochemical (IHC) analysis was performed on 57 primary tumor samples obtained from ESCC patients who underwent curative esophagectomy between 1999 and 2009 in Kyoto Prefectural University of Medicine. Results: In an in vitro study, the depletion of ANO9 reduced cell proliferation, invasion and migration in KYSE150 and KYSE 790 cells. And, the depletion of ANO9 increased the number of cells in G0/G1 arrest and induced apoptosis in these cells. The results of the microarray analysis indicated that various centrosome-related genes such as CEP120, CNTRL and SPAST, were up- or down-regulated in ANO9-depleted KYSE150 cells. The IHC results showed that high expression of ANO9 was independent prognostic factor in ESCC patients (p = 0.025). Conclusion: ANO9 played the important role in the cell cycle and progression of ESCC cells through the expression of centrosome-related genes. In addition, the high expression of ANO9 was a poor prognostic factor in ESCC patients. The results of the present study indicate that ANO9 has potential as a biomarker for cancer growth and as a therapeutic target for ESCC such as inhibitor or RNA interference of ANO9.